Thoughts of Biology Virtual Lab: A Meta-analysis study of Urogenital System Practicum in Universitas Terbuka - Kismiati, Dyah Aniza; Kusmawan, Udan; Hutasoit, Leonard R. (Universitas Terbuka, 2022)
Practicum is an essential part of the student learning process. It promotes strengthening scientific process skills to students. On the other hand, limited access in experiencing hands-on activities requires serious attention due to the characteristics of a distance education system that restrains face-to-face activities in student learning. For this reason, a virtual lab is necessary to meet the needs of students to comprehend the functions of scientific actions while their learning. The paper will discuss the role of a virtual lab in the Biology practicum in Universitas Terbuka (UT). This paper is a meta-analysis study involving preliminary data of UT students who attended biology practicum courses during the Covid-19 pandemic. The research recommends using the virtual Lab to advance biological knowledge in biology practicum and Virtual Reality as suitable for urogenital system material. The use of 3D simulation in Virtual Reality should provide an exciting and meaningful learning experience for students.